Comparison and appraisal of (inter)national recurrent pregnancy loss guidelines. Issue 3 (September 2019) - Youssef, Angelos; Vermeulen, Nathalie; Lashley, E.E. Lisa O.; Goddijn, Mariëtte; van der Hoorn, Marie Louise P.
Abstract: Investigations and treatment options of recurrent pregnancy loss (RPL) differ internationally. This manuscript reviews the similarities and differences between international guidelines. The European Society of Human Reproduction and Embryology (ESHRE) guideline (2017), the American Society for Reproductive Medicine (ASRM) Committee Opinion (2013) and the Royal College of Obstetricians and Gynaecologists (RCOG) guideline (2011) were appraised using the AGREE II criteria. The guidelines were checked for definitions, risk factors, investigations and therapeutic options. The guidelines agreed on acquired thrombophilia analysis. All guidelines agreed on a regimen for the treatment of antiphospholipid antibody syndrome consisting of aspirin and heparin, but only the ESHRE guideline specified the order of starting these medications. Treatment of thrombophilia and uterine anomalies was advised against; all guidelines recommended supportive care for unexplained RPL. The guidelines did not agree on the definition of RPL and differed in investigations regarding lifestyle, karyotype analysis of parents and/or pregnancy tissue, and the diagnostic tool for uterine anomalies. All three guidelines indicate an association between lifestyle and RPL; the ESHRE recommends health behaviour changes. Couples suffering from RPL should be informed about possible investigations and treatment options, and whether those are evidence-based. It is important for clinicians to realize that the guidelines differ internationally. Graphical Abstract: Image, graphical abstract